Peran Media Pembelajaran APE “Puzzle Tempel Huruf” Terhadap Kemampuan Membaca Siswa Kelas 1 SD Negeri Semin III - Triwinarti, Anik; Henu Cahyani , Berliana; Sudigdo, Anang (GERAM, 2024)
The Indonesian language is the official language used in Indonesia. Good and proper reading skills in Indonesian are crucial for students, especially first-grade elementary school students. Reading is a fundamental skill that students must master to access information from various sources and understand multiple subjects well. APE "Letter Puzzle Sticker" is an instructional media or learning tool that uses a game-based learning approach. This research aims to determine the role of instructional media APE "Letter Puzzle Sticker" in improving the reading abilities of first-grade students at Semin III Elementary School in Gunungkidul Regency, as well as the benefits of using APE letter puzzle sticker media in enhancing the reading abilities of first-grade students. This research uses a qualitative descriptive method with one research subject. The instruments used in this research are observation sheets and interviews. The results of this research show that students can recognize letters, build words through pictures, and read. The research emphasizes the importance of selecting letters or words that match students' difficulty levels and implementing effective learning techniques. This conclusion contributes to a better understanding of the role of instructional media in improving the reading skills of first-grade students.